Introduction to Enzyme Immobilization - Roshanida, A. Rahman; Shalyda, Md Shaarani (Penerbit UTM, 2022)
Recent advances in biotechnology and bioengineering have shown an increasing trend towards the development of environmentally friendly, safe and sustainable bioprocesses using enzymes. The excellent selectivity, specificity and catalytic performance have made enzymes robust biocatalysts with a wide range of applications in biomedicine, biosensing, and biocatalysis (Bilal et al., 2021). Due to the low use of chemicals and the absence of hazardous metabolites/byproducts, the use of biocatalysts is expected to facilitate environmentally friendly processes. In addition, there is a recurring obstacle in the various industries where biocatalysis can be used: the application of enzyme catalysis in chemical processes is limited by the lack of stability of enzymes at high temperatures or in turbulent flow regimes, as well as in potentially toxic solvents (Chapman et al., 2018)